Frontline Science: Structural insights into Resolvin D4 actions and further metabolites via a new total organic synthesis and validation. Issue 6 (29th January 2018) - Winkler, Jeremy W.; Libreros, Stephania; De La Rosa, Xavier; Sansbury, Brian E.; Norris, Paul C.; Chiang, Nan; Fichtner, David; Keyes, Gregory S.; Wourms, Nicholas; Spite, Matthew; Serhan, Charles N.
Abstract: Local production and downstream metabolism of specialized proresolving lipid mediators (SPMs) are pivotal in regulating their biological actions during resolution of inflammation. Resolvin D4 (RvD4: 4 S, 5 R, 17 S ‐trihydroxydocosa‐6 E, 8 E, 10 Z, 13 Z, 15 E, 19 Z hexaenoic acid) is one of the more recently elucidated SPMs with complete stereochemistry biosynthesized from docosahexaenoic acid. Here, we report a new multimilligram commercial synthesis that afforded enough material for matching, validation, and further evaluation of RvD4 functions. Using LC‐MS‐MS profiling, RvD4 was identified at bioactive amounts in human (1 pg/mL) and mouse bone marrow (12 pg/femur and tibia). In mouse bone marrow, ischemia increased the formation of RvD4 > 37‐fold (455 pg/femur and tibia). Two separate mouse ischemic injury models were used, where RvD4 reduced second organ reperfusion lung injury > 50%, demonstrating organ protection. Structure–function relationships of RvD4 demonstrated > 40% increase in neutrophil and monocyte phagocytic function in human whole blood in comparison with 2 separate trans‐containing double bond isomers that were inactive. These 2 isomers were prepared by organic synthesis: 4 S, 5 R, 17 S ‐trihydroxydocosa‐6 E, 8 E, 10 E, 13 Z, 15 E, 19 Z ‐hexaenoic acid (10‐trans‐RvD4), a natural isomer, and 4 S, 5 R, 17 S ‐trihydroxydocosa‐6 E, 8 E, 10 E, 13 E, 15 E, 19 Z ‐hexaenoic acid (10, 13‐trans‐RvD4), a rogue isomer. Compared to leukotriene B4, D‐series resolvins (RvD1, RvD2, RvD3, RvD4, or RvD5) did not stimulate human neutrophil chemotaxis monitored via real‐time microfluidics chambers. A novel 17‐oxo‐containing‐RvD4 product of eicosanoid oxidoreductase was identified with human bone marrow cells. Comparison of 17‐oxo‐RvD4 to RvD4 demonstrated that with human leukocytes 17‐oxo‐RvD4 was inactive. Together, these provide commercial‐scale synthesis that permitted a second independent validation of RvD4 complete stereochemical structure as well as evidence for RvD4 regulation in tissues and its stereoselective phagocyte responses. Abstract : Resolvin D4 commercial‐scale total organic synthesis elucidates new functions.